Briquetting of Fine‐Grained Residues from Iron and Steel Production Using Organic and Inorganic Binders. Issue 12 (29th July 2020) - Lohmeier, Laura; Thaler, Christoph; Harris, Christopher; Wollenberg, Ralf; Schröder, Hans-Werner
Abstract : The Midrex process produces metallurgical residues in the form of dust, sludge, and fines. As these have high iron content, herein, the aim is to recycle the residues and use them as an educt in the Midrex process, thus closing the material cycle and increasing raw material efficiency. Briquetting of these materials with binder is one possibility to prepare them for the use as an educt in the Midrex process. Experiments are conducted to test the suitability of the organic binders starch and cellulose for briquetting. Furthermore, tests with the inorganic bentonite are included for comparison. Briquettes are generally characterized by high strength. However, compared with iron oxide pellets, they have a low porosity and thus a higher apparent density, and consequently, a worse reducibility. The use of organic binders should improve the reducibility. The iron oxides are in close contact with the C‐carrier of the organic binder so that a solid–solid phase direct reduction can take place. Furthermore, the solid carbon reacts to CO, and thus, increases the presence of reducing gas in the enlarged pores of the briquettes, and should therefore increase the degree of reduction. Abstract : The Midrex direct reduction process produces a number of ferrous, fine‐grained residues. To avoid disposal, a way of briquetting the residues with binder and returning them to the Midrex direct reduction process is demonstrated. Laboratory‐scale briquetting experiments with inorganic and organic binders are presented and their suitability is compared with regard to the mechanical and metallurgical properties of the briquettes.